Research methods for managers - Gill, John, 1930- John Gill; Johnson, Phil, 1955-; Clark, Murray (Los Angeles : SAGE, 2010)
This edition provides a step-by-step guide to implementing particular methodologies, while simultaneously encouraging a strong awareness of philosophical assumptions.
Previous ed.: 2002.
Includes bibliographical references (p. [243]-259) and index.
Keywords: Management -- Research -- Methodology; Industrial management -- Research -- Methodology; Business and Management